Colleges and schools-College of Arts and Humanities-Music-0003
Melvin Baddin, Csuf Violin Teacher and AC Berdahl examine a rare (1731) Guarnerins loaned to Baddin by the Philip (and two Torture bows) Farrar family with Fresno Bee Oct. 29, 1951 Loan recalled by Mrs. Farrar in 1953/4 to sell to someone to give to micha